Perbandingan validitas alat ukur nyeri antara Self-report pain scale dan observational pain scale Pada nyeri akut anak usia 3-7 tahun - Dede - Renolvadi; Riri - Novayelinda; Siti Rahmalia HD (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2014)
The purpose of this study was to compare the validity of pain scales between self-report pain scale and observational pain scale in acute pain of 36 children aged 3-7 years old receiving intravenous canullation procedure in pediatric unit at Arifin Achmad General Hospital. This study was an observational analitical study toward diagnostic test. This study design was cross-sectional with consecutive sampling method. The level of pain was measured by using Faces Pain Rating Scale (FPRS) as self-report method and FLACC scale as observational method. CHEOPS was used as the gold-standard. The data were analysed by using concurrent validity, sensitivity-specificity, and Receiver Operating Characteristic (ROC) curve. In concurrent validity, FLACC showed a better positive correlation compared to FPRS (r=0.946 : r=0.387). FLACC also had higher value of sensitivity and specificity (100%, 95%) which were higher compared to FPRS (93%, 40%). ROC analysis also showed higher value of the Area Under Curve (AUC) of FLACC (100%) compared to FPRS (89.4%). The result of this study performed a statistically better validity for FLACC as an observational pain scale to measure acute pain of children aged 3-7 years old. This study suggests the using of FLACC as the better scale in pain assessment of children aged 3-7 years old. Keyword: Acute pain, children, FPRS scale, FLACC scale, validity.